2020
DOI: 10.1038/s41467-019-14082-5
|View full text |Cite
|
Sign up to set email alerts
|

The epichaperome is a mediator of toxic hippocampal stress and leads to protein connectivity-based dysfunction

Abstract: Optimal functioning of neuronal networks is critical to the complex cognitive processes of memory and executive function that deteriorate in Alzheimer’s disease (AD). Here we use cellular and animal models as well as human biospecimens to show that AD-related stressors mediate global disturbances in dynamic intra- and inter-neuronal networks through pathologic rewiring of the chaperome system into epichaperomes. These structures provide the backbone upon which proteome-wide connectivity, and in turn, protein n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
207
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(220 citation statements)
references
References 67 publications
4
207
0
Order By: Relevance
“…Furthermore, STI1/ Hop loss of function in Drosophila overexpressing the full-length 2 N/4R isoform of wild-type human tau in the eye, resulted in significant loss of retinal cells [107]. Recently, Inda et al [40] demonstrated that in AD, chaperones associate to form large stable complexes, termed epichaperomes, that no longer regulate client protein function. These epichaperomes impaired protein connectivity, proteostasis, and synaptic plasticity in their AD mouse models [40], which could be corrected by disassembly of epichaperomes by an Hsp90 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, STI1/ Hop loss of function in Drosophila overexpressing the full-length 2 N/4R isoform of wild-type human tau in the eye, resulted in significant loss of retinal cells [107]. Recently, Inda et al [40] demonstrated that in AD, chaperones associate to form large stable complexes, termed epichaperomes, that no longer regulate client protein function. These epichaperomes impaired protein connectivity, proteostasis, and synaptic plasticity in their AD mouse models [40], which could be corrected by disassembly of epichaperomes by an Hsp90 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Inda et al [40] demonstrated that in AD, chaperones associate to form large stable complexes, termed epichaperomes, that no longer regulate client protein function. These epichaperomes impaired protein connectivity, proteostasis, and synaptic plasticity in their AD mouse models [40], which could be corrected by disassembly of epichaperomes by an Hsp90 inhibitor. Since Hsp90, Hsp70 and STI1 are all members of these epichaperomes in AD tissues, it may be important to test in the future how increased or decreased levels of STI1 regulate epichaperomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9). The inability of neurons to cope with accumulating tau pathology is hypothesized to stimulate formation of a dysfunctional epichaperome (high molecular weight complexes composed of HSP90 and HSP70 chaperones) and render neurons prone to degeneration 29 . The strong transcriptional response of HSPs in AstAD prompted us to test whether improving chaperone function by dispersing the dysfunctional epichaperome could delay disease progression.…”
Section: Main Textmentioning
confidence: 99%
“…For instance, epichaperomes, i.e. metastable chaperone networks stabilized by Hsp90, seem to promote the accumulation and toxicity of misfolded tau (21). Experiments using purified proteins have shown that Hsp90 has the capacity to both inhibit TDP-43 aggregation and to convert TDP-43 aggregates into more soluble species (22).…”
Section: Introductionmentioning
confidence: 99%